Interventions for recurrent corneal erosions - Stephanie L Watson; Ming‐Han H Lee; Nigel H Barker (Cochrane Database of Systematic Reviews, 2012)
BACKGROUND: Recurrent corneal erosion is a common cause of disabling ocular symptoms and predisposes the cornea to infection. It may follow corneal trauma. Measures to prevent the development of recurrent corneal erosion following corneal trauma have not been firmly established. Once recurrent corneal erosion develops simple medical therapy (standard treatment) may lead to resolution of the episode. However, some patients continue to suffer when such therapy fails and once resolved further episodes of recurrent erosion may occur. A number of treatment and prophylactic options are then available but there is no agreement as to the best option. OBJECTIVES: To assess the effectiveness and safety of prophylactic and treatment regimens for recurrent corneal erosion. SEARCH METHODS: We searched CENTRAL (which contains the Cochrane Eyes and Vision Group Trials Register) (The Cochrane Library 2012, Issue 6), MEDLINE (January 1946 to June 2012), EMBASE (January 1980 to June 2012), Latin American and Caribbean Literature on Health Sciences (LILACS) (January 1982 to June 2012), the metaRegister of Controlled Trials (mRCT) (www.controlled-trials.com), ClinicalTrials.gov (www.clinicaltrials.gov) and the WHO International Clinical Trials Registry Platform (ICTRP) (www.who.int/ictrp/search/en). We did not use any date or language restrictions in the electronic searches for trials. We last searched the electronic databases on 13 June 2012. We also contacted researchers in the field. SELECTION CRITERIA: We included randomised and quasi-randomised trials that compared a prophylactic or treatment regimen with another prophylaxis/treatment or no prophylaxis/treatment for patients with recurrent corneal erosion. DATA COLLECTION AND ANALYSIS: Two authors independently extracted data and assessed trial quality. We contacted study authors for additional information. MAIN RESULTS: Seven randomised and one quasi-randomised controlled trial were included in the review. The trials were heterogenous and of poor quality. Safety data presented were incomplete. For the treatment of recurrent corneal erosion, a single-centre trial in the UK with 30 participants showed that oral tetracycline 250 mg twice daily for 12 weeks or topical prednisolone 0.5% four times daily for one week, or both, in addition to standard treatment, accelerated healing rates and improved symptoms. A single-centre trial in Sweden with 56 participants showed that excimer laser ablation in addition to mechanical debridement may reduce the number of erosions and improve symptoms. Furthermore, in a single-centre trial in Germany with 100 participants, transepithelial technique for excimer laser ablation had the same efficacy as the traditional subepithelial excimer laser technique but caused less pain. In a small study of 24 participants in UK, therapeutic contact lens wear was inferior to lubricant drops and ointment in abolishing the symptoms of recurrent corneal erosion and had a high complication rate, although the contact lenses used were the older generation with low oxygen permeability. A recent study in Hong Kong with 48 participants found diamond burr polishing to reduce episodes of recurrent corneal erosion. For prophylaxis of further episodes of recurrent corneal erosion, there was no difference in the occurrence of objective signs of recurrent erosion between hypertonic saline ointment versus tetracycline ointment or lubricating ointment in a small Japanese study with 26 participants. Also, in a single-centre study in the UK with 117 participants, there was no difference in symptom improvement between hypertonic saline versus paraffin ointment when used for prophylaxis. In a UK study with 42 participants, lubricating ointment at night in addition to standard treatment to prevent recurrence following traumatic corneal abrasion (erosion) caused by fingernail injury led to increased symptoms of recurrent corneal erosion compared to standard therapy alone. AUTHORS' CONCLUSIONS: Well-designed, masked, randomised controlled trials using standardised methods are needed to establish the benefits of new and existing prophylactic and treatment regimes for recurrent corneal erosion. International consensus is also needed to progress research efforts towards evaluation of the major effective treatments for recurrent corneal erosions.